Evaluation of instructional material while in use: Welcome to Brazil, Level 1 - Masin, Maria Angela (The ESPecialist, 2014)
The aim of this paper is to evaluate the use of the instructional material Welcome to Brazil - Level 1 (Fenton and McLarty, 2011) in a technological course in Tourism Management in the city of São Paulo. The textbook content was evaluated according to Ramos (2009) and a questionnaire was used to collect the students’ impressions. It was concluded that the textbook needs to be complemented for an effective result with the students. The theoretical foundation is based on Cunningsworth (1984), Hutchinson and Waters (1987), Dudley-Evans and St. John (1998), Tomlinson (1998, 2001), Ramos (2009).